An Unusual Case of Bony Styloid Processes That Extend to the Hyoid Bone - Shekhar K. Gadkaree; Christopher G. Hyppolite; Aisha Harun; Ryan H. Sobel; Young Kim (Case Reports in Otolaryngology, 2015)
The embryological origin of the hyoid bone is a point of uncertainty, with controversy surrounding the relative contribution of the second pharyngeal arch to hyoid development. We encountered a 52-year-old male with bilateral bony styloid extension to the lesser cornu of the hyoid bone during the workup of a patient with laryngeal cancer. This embryological malformation clearly supports the hypothesis that the second pharyngeal arch gives rise to the lesser cornu and demonstrates an unusual clinical finding that may be encountered by otolaryngologists. We demonstrate the imaging findings and surgical management of this unusual anatomical variant and review the embryological basis for this rare malformation.